Perceptions of young offenders about the police: a qualitative study conducted in Brazil - Balisardo Coelho, Jéssica; Sandro Gomes Pessoa, Alex; Bottrell, Dorothy (Revista Pesquisas e Práticas Psicossociais, 2017)
The objective of this article is to better understand young offenders' perceptions of the police, as well as to investigate how the context of police violence is implicated in the process of criminalization of this group. A qualitative study was conducted with young offenders who have had experiences of being policed within their development contexts. From an ecological approach, we emphasize the psychosocial dimensions of adolescent experiences within a systemic model of violence. The findings highlighted the damaging effects of truculent police approaches in adolescents' lives and how such actions reinforce the social stigmas that accompany young people exposed to social exclusion, undermining the rights ensured by the Child and Adolescent Statute. Keywords: Adolescence. Police. Young offenders. Violence. Psychosocial.